DEVELOPMENT OF MATHEMATICS MODULE FOR CLASS VII WITH SCIENCE APPROACH IN PROPORTION MATERIAL - Desi Kusuma Wardani; Suparman Suparman (Universitas Ahmad Dahlan, 2019)
Students must be active and independent in the learning process and understand the material studied in learning mathematics. The mathematical module is one of the alternative learning resources that can be used in the learning process. The research aims to develop a mathematical module of comparative material with a scientific approach for grade VII students of Junior High School (SMP / MTs) applied correctly in mathematics learning. This development research uses Research and Development (R & D) method. Such research subjects include material experts, media experts, students from 2 schools. Data collection techniques used are interviews and questionnaires. The research instruments are questionnaires, which have been reviewed. Types of data used are qualitative and quantitative data. The result of mathematics-module research and development of proportion material with a scientific approach for class VII SMP students. The results of the material feasibility test included the right criteria, with an average score of 67. The media feasibility test module media included in the right criteria with an average score of 67.67. Simultaneously, the small-class product trial stage's student response questionnaire was included in the right criteria, with an average score of 64,7. The student response questionnaire of the big-class product's trial stage includes perfect criteria, with an average score of 70,2. These results indicate that the mathematics module of comparative material with a scientific approach for grade VII students of SMP/MTs is feasible for the learning process.